NaCl and osmolarity produce different responses in organum vasculosum of the lamina terminalis neurons, sympathetic nerve activity and blood pressure. (2nd August 2017) - Kinsman, Brian J.; Browning, Kirsteen N.; Stocker, Sean D.
Abstract : Key points: Changes in extracellular osmolarity stimulate thirst and vasopressin secretion through a central osmoreceptor; however, central infusion of hypertonic NaCl produces a greater sympathoexcitatory and pressor response than infusion of hypertonic mannitol/sorbitol. Neurons in the organum vasculosum of the lamina terminalis (OVLT) sense changes in extracellular osmolarity and NaCl. In this study, we discovered that intracerebroventricular infusion or local OVLT injection of hypertonic NaCl increases lumbar sympathetic nerve activity, adrenal sympathetic nerve activity and arterial blood pressure whereas equi‐osmotic mannitol/sorbitol did not alter any variable. In vitro whole‐cell recordings demonstrate the majority of OVLT neurons are responsive to hypertonic NaCl or mannitol. However, hypertonic NaCl stimulates a greater increase in discharge frequency than equi‐osmotic mannitol. Intracarotid or intracerebroventricular infusion of hypertonic NaCl evokes a greater increase in OVLT neuronal discharge frequency than equi‐osmotic sorbitol. Collectively, these novel data suggest that subsets of OVLT neurons respond differently to hypertonic NaCl versus osmolarity and subsequently regulate body fluid homeostasis. These responses probably reflect distinct cellular mechanisms underlying NaCl‐ versus osmo‐sensing. Abstract: Systemic or central infusion of hypertonic NaCl and other osmolytes readily stimulate thirst and vasopressin secretion. In contrast, central infusion of hypertonic NaCl produces a greater increase in arterial blood pressure (ABP) than equi‐osmotic mannitol/sorbitol. Although these responses depend on neurons in the organum vasculosum of the lamina terminalis (OVLT), these observations suggest OVLT neurons may sense or respond differently to hypertonic NaCl versus osmolarity. The purpose of this study was to test this hypothesis in Sprague‐Dawley rats. First, intracerebroventricular (icv ) infusion (5 μl/10 min) of 1.0 m NaCl produced a significantly greater increase in lumbar sympathetic nerve activity (SNA), adrenal SNA and ABP than equi‐osmotic sorbitol (2.0 osmol l −1 ). Second, OVLT microinjection (20 nl) of 1.0 m NaCl significantly raised lumbar SNA, adrenal SNA and ABP. Equi‐osmotic sorbitol did not alter any variable. Third, in vitro whole‐cell recordings demonstrate that 50% (18/36) of OVLT neurons display an increased discharge to both hypertonic NaCl (+7.5 mm ) and mannitol (+15 mm ). Of these neurons, 56% (10/18) displayed a greater discharge response to hypertonic NaCl vs mannitol. Fourth, in vivo single‐unit recordings revealed that intracarotid injection of hypertonic NaCl produced a concentration‐dependent increase in OVLT cell discharge, lumbar SNA and ABP. The responses to equi‐osmotic infusions of hypertonic sorbitol were significantly smaller. Lastly, icv infusion of 0.5 m NaCl produced significantly greater increases in OVLT discharge and ABP thanicv infusion of equi‐osmotic sorbitol. Collectively, these findings indicate NaCl and osmotic stimuli produce different responses across OVLT neurons and may represent distinct cellular processes to regulate thirst, vasopressin secretion and autonomic function. Key points: Changes in extracellular osmolarity stimulate thirst and vasopressin secretion through a central osmoreceptor; however, central infusion of hypertonic NaCl produces a greater sympathoexcitatory and pressor response than infusion of hypertonic mannitol/sorbitol. Neurons in the organum vasculosum of the lamina terminalis (OVLT) sense changes in extracellular osmolarity and NaCl. In this study, we discovered that intracerebroventricular infusion or local OVLT injection of hypertonic NaCl increases lumbar sympathetic nerve activity, adrenal sympathetic nerve activity and arterial blood pressure whereas equi‐osmotic mannitol/sorbitol did not alter any variable. In vitro whole‐cell recordings demonstrate the majority of OVLT neurons are responsive to hypertonic NaCl or mannitol. However, hypertonic NaCl stimulates a greater increase in discharge frequency than equi‐osmotic mannitol. Intracarotid or intracerebroventricular infusion of hypertonic NaCl evokes a greater increase in OVLT neuronal discharge frequency than equi‐osmotic sorbitol. Collectively, these novel data suggest that subsets of OVLT neurons respond differently to hypertonic NaCl versus osmolarity and subsequently regulate body fluid homeostasis. These responses probably reflect distinct cellular mechanisms underlying NaCl‐ versus osmo‐sensing.